Hubungan antara Pengetahuan Ibu Pasca Persalinan tentang Pijat Woolwich dan Penambahan Berat Badan Bayi di Klinik Alisah pada Tahun 2025 - Ritonga, Juliana Safitri; Nasution, Ria Niari; Sinaga, Meiyana; Hasibuan, Namiroh Falah; Simanungkalit, Ermita Silvana Putri; Sihombing, Eni Monaliska; Halawa, Gustiani (Yayasan Amanah Nur Aman, 2025)
Woolwich massage is a stimulation for breastfeeding mothers that provides a sense of relaxation and comfort, thereby increasing prolactin hormones and breast milk production, which is the main source of nutrition for babies. Exclusive breastfeeding for the first six months, followed by complementary foods until the age of two, plays an important role in the growth of babies, including weight gain. This study aims to determine the relationship between postpartum mothers' knowledge of Woolwich massage and infant weight gain at the Alisah Clinic in 2025. The study design uses an analytical approach with total sampling techniques, involving the entire population of 30 postpartum mothers who underwent Woolwich massage. The results show that the majority of mothers had poor knowledge (14 people, 46.7%), while a minority had good knowledge. The majority of infants did not experience weight gain, namely 23 infants (76.7%), while 7 infants (23.3%) experienced weight gain. Statistical testing at a 95% confidence level yielded a p-value of 0.00 < 0.01, indicating a significant relationship between postpartum mothers' knowledge of Woolwich massage and infant weight gain. The conclusion of this study confirms that postpartum mothers' knowledge influences the success of Woolwich massage in supporting infant growth. It is recommended that postpartum mothers routinely perform Woolwich massage to increase breast milk production, thereby stimulating growth and becoming an important factor in infant weight gain.